2012
DOI: 10.5455/vetworld.2012.718-722
|View full text |Cite
|
Sign up to set email alerts
|

Meat inspection and animal welfare practices: Evidences from north-western Himalayan region, India

Abstract: Aim: The present study was conducted to assess the animal welfare measures for safe and wholesome meat production as well to understand different roles performed by delegated institutions in ensuring quality meat production. Materials and Methods: Semi-structured interview schedule was administered to 40 butchers and 40 veterinary officers of state department of animal husbandry, Himachal Pradesh. Result: It was found that open slaughtering was common (87.50%), animals did not have sufficient water provisions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…Our observations and questionnaires identified the slaughter places as an important source of contamination with faeces because of processing on the floor, lack of adequate water and waste disposal, and poor practices by slaughterhouse workers. Similar problems are seen in many parts of India, where slaughter is often without running water or basic separation into a dirty and a clean compartment [31]. Substantial investments in infrastructure are often needed to assure food safety, but funding is rarely available.…”
Section: Discussionmentioning
confidence: 93%
“…Our observations and questionnaires identified the slaughter places as an important source of contamination with faeces because of processing on the floor, lack of adequate water and waste disposal, and poor practices by slaughterhouse workers. Similar problems are seen in many parts of India, where slaughter is often without running water or basic separation into a dirty and a clean compartment [31]. Substantial investments in infrastructure are often needed to assure food safety, but funding is rarely available.…”
Section: Discussionmentioning
confidence: 93%
“…Although meat inspection is mandatory in India, it is clear that in some areas it is carried out in a somewhat desultory manner (e.g. [14]) – and it is of probable relevance that a ranking exercise among a group of biomedical students in Chandigarh revealed that the profession of veterinarian is considered to be of very low status [15]. However, even if conducted carefully, routine carcass inspection is likely to miss light infections [16].…”
Section: Discussionmentioning
confidence: 99%
“…Beef is however poorly handled right from slaughtering, transportation and trading of the meat. Poor handling and inspection of beef produced is one of the most important causes of human deaths worldwide as a result of contaminants [2]. Many of the recent zoonotic infections have originated from animal or from products of animal origin [2].…”
Section: Introductionmentioning
confidence: 99%
“…Poor handling and inspection of beef produced is one of the most important causes of human deaths worldwide as a result of contaminants [2]. Many of the recent zoonotic infections have originated from animal or from products of animal origin [2]. Beef contains sufficient nutrients needed to support the growth of micro-organisms [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation